THE EFFECTS OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CLIMATE ON THE PERFORMANCE OF EMPLOYEES AT PUSAT PAUD ISLAM TERPADU AL ISHLAH GORONTALO - Ibrahim, Arlin Siswaty; Abdussamad, Zuchri; Hanafi, Hanisah (Public Policy Journal, 2020)
ABSTRACTThis study aims to determine the effects of transformational leadership and organizational climate on the performance of employees at the Islamic Center of Integrated Al Ishlah Gorontalo partially and simultaneously. The approach in this research is quantitative. The research method is ex post facto. The design of this research is causality. The data analysis technique used is multiple regression. The results show that (1) Transformational leadership has a positive and significant effect on the performance of Al Ishlah Gorontalo Islamic Integrated Islamic Center employees with a determinant coefficient of 36.40%. (2) Organizational climate has a positive and significant effect on the performance of Al Ishlah Gorontalo Islamic Integrated Islamic Education Center employees with a determinant coefficient of 22.80%. (3) Transformational leadership and organizational climate have a positive and significant impact on the performance of Al Ishlah Gorontalo Islamic Integrated Islamic Center staff with a determinant coefficient of 59.20%. Meanwhile, the remaining 40.80% is influenced by other factors not explained in this study; such as job training, work motivation, work discipline, and others.